Cross-institutional synergy in bioactive compound research: a same-city multi-university collaborative framework in Zaporizhzhia, Ukraine - Antypenko, L.; Antypenko, O. M.; Brytanova, T. S.; Антипенко, Олексій Миколайович; Британова, Тетяна Сергіївна (My University, 2025)
The paper proposes the framework for inter-university collaboration, focusing on the potential integration of three major universities of Zaporizhzhia, Ukraine. The study observes the impact of academic partnerships through a comprehensive assessment of resource optimization, educational enhancement, and innovation capabilities. The five-phase integration model, designed for investigation of novel biologically active substances, demonstrates how coordinated academic efforts can maintain educational excellence and research productivity even under challenging circumstances, while creating a foundation for sustained scientific development.